2016
DOI: 10.1016/j.vaccine.2016.04.096
|View full text |Cite
|
Sign up to set email alerts
|

Do we have enough evidence how seasonal influenza is transmitted and can be prevented in hospitals to implement a comprehensive policy?

Roger E. Thomas

Abstract: HCW vaccination is a partial solution with current vaccination levels. There are no RCTs of screening HCWs, patients and visitors demonstrating preventing influenza transmission. Only one study costed furloughing HCWs with influenza and no RCTs have identified benefits of isolating influenza supershedders. RCTs of directly- and electronically continuously-observed mask-wearing and hand-hygiene and RCTs of incentives for meticulous hygiene are required. RCTs of engineering solutions (external venting, frequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…[26][27][28][29][30][31] However, most influenza transmission is short-range, and when it has occurred over longer distances, contact transmission has generally not been ruled out. 32 Transmission studies often do not control for confounders such as vaccination status, handwashing practice, supershedders, amount of coughing, ward layout, surface contamination and ventilation, 33 and further studies which control for these are required in this area.…”
Section: Outbreaks Of Influenza (And Other Respiratory Virus Pathogenmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29][30][31] However, most influenza transmission is short-range, and when it has occurred over longer distances, contact transmission has generally not been ruled out. 32 Transmission studies often do not control for confounders such as vaccination status, handwashing practice, supershedders, amount of coughing, ward layout, surface contamination and ventilation, 33 and further studies which control for these are required in this area.…”
Section: Outbreaks Of Influenza (And Other Respiratory Virus Pathogenmentioning
confidence: 99%
“…Compliance with these measures may be an issue and there is currently a paucity of directly observed studies of handwashing and mask-wearing. 33 There is some evidence that the wearing of a surgical face mask by an infected person decreases their infectiousness to others 108,109 and may be considered for infected LTCF residents, particularly if they have to be moved outside their own room or cohort area; although in reality this measure may not be tolerated by some individuals. Residents sharing a room with an influenza-infected roommate have three times the risk of acquiring infection than those in single rooms.…”
Section: Outbreak Control Measuresmentioning
confidence: 99%
“…Seasonal influenza occurs in epidemic peaks during the winter periods. Particular climate conditions, including cold and humidity, school holidays, and the characteristics of the likely circulating viral strain and vaccination coverage, are associated with epidemic peaks that vary in intensity in terms of the number of patients and the severity of the observed cases [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infectious diseases account for millions of school-days lost each year among kindergarteners; for instance, kindergarteners with flu missed approximately 38 million school-days each year in the United States. 1 Many studies have been conducted to find ways to minimize the loss, and frequent hand hygiene has been found effective in preventing the spread of infectious organisms 2 and it remains the most important defense against diseases. 3 A recent study Or et al 4 on kindergarteners demonstrated an improvement in their hand hygiene routine markedly after receiving training.…”
Section: Introductionmentioning
confidence: 99%